Hepatobiliary Disorders in Celiac Disease: An Update. (11th October 2010) - Prasad, Kaushal K.; Debi, Uma; Sinha, Saroj K.; Nain, Chander K.; Singh, Kartar
Abstract : This communication reviews recent literature and summarizes hepatobiliary abnormalities that may complicate the clinical course of celiac disease. A wide spectrum of hepatobiliary diseases has been described, including asymptomatic elevations of liver enzyme levels, nonspecific hepatitis, nonalcoholic fatty liver disease, and autoimmune and cholestatic liver disease. Moreover, in the majority of patients, liver enzyme levels will normalize on a gluten-free diet. In addition, celiac disease may be associated with rare hepatic complications, such as hepatic T-cell lymphoma. Because many celiac patients do not have overt gastrointestinal symptoms, a high index of suspicion is required. Simple methods of detecting celiac disease such as serum antibody tests help in the early identification of the disease, thus preventing serious complications of the disorder. The IgG DGP antibody test and IgA tTG antibody test used in combination are an excellent screening test for suspected cases of celiac disease.